(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
Textile wet processing is the most polluting aspect of textile manufacturing and contributes to the global textile industry's substantial carbon footprint. Textile preparation of cotton typically includes scouring and bleaching at high temperature and high pH. Substantial amounts of wastewater are produced that must be treated prior to being released to receiving fresh water. Recent research in our laboratories has focused on the development and application of compounds that enhance the bleaching process. We have developed novel cationic bleach activators that can be used to bleach cellulosic fabrics and fiber blends at reduced temperature, pH, and time. Results show that after optimization equivalent or improved performance in whiteness, absorbency and strength are possible relative to conventional bleaching methods. One of the most promising bleach activators to date is N-[4-(Triethylammoniomethyl) Benzoyl]-Butyrolactam Chloride (TBBC). TBBC was designed in our group to a) exhibit strong oxidation potential when activated; b) have reasonable hydrolytic stability; and c) be inherently substantive towards cellulosic and other fibers. In this paper, we review the development of bleach activators for textile bleaching, and discuss the opportunities and potential hurdles involved in commercialization of bleach activators for textile wet processing.